Exceptional tumour responses to fasting-mimicking diet combined with standard anticancer therapies: A sub-analysis of the NCT03340935 trial. (September 2022) - Ligorio, Francesca; Fucà, Giovanni; Provenzano, Leonardo; Lobefaro, Riccardo; Zanenga, Lucrezia; Vingiani, Andrea; Belfiore, Antonino; Lorenzoni, Alice; Alessi, Alessandra; Pruneri, Giancarlo; de Braud, Filippo; Vernieri, Claudio
Abstract: Background: Cyclic fasting or calorie-restricted, low-carbohydrate, low-protein diets, collectively referred to as fasting-mimicking diets (FMDs), demonstrated additive or synergistic antitumour effects when combined with chemotherapy, targeted therapies, or immunotherapy in several preclinical in vivo models, including murine models of breast cancer, lung cancer, and colorectal cancer. However, no data on the antitumour efficacy of cyclic FMD in patients with cancer have been published so far. Here, we aim at reporting on patients with advanced cancer achieving complete and long-lasting tumour remissions with cyclic FMD in combination with standard anticancer therapies in the context of the phase Ib NCT03340935 trial. Patients and methods: The NCT03340935 trial enrolled 101 patients with different tumour types, and it showed that a severely calorie-restricted FMD regimen is safe and feasible in patients with cancer receiving concomitant standard-of-care antineoplastic therapies. In addition, cyclic FMD resulted in positive metabolic and immunologic modifications, thus recapitulating the biological effects that in preclinical models were found to mediate the antitumour effects of fasting/FMD. Results: Of the 101 patients enrolled in the NCT03340935 trial, we identified five patients with advanced, poor prognosis solid neoplasms (n = 1: extensive stage small cell lung cancer; n = 1: metastatic pancreatic adenocarcinoma; n = 1: metastatic colorectal cancer; n = 2: metastatic triple-negative breast cancer), who achieved complete and long-lasting tumour responses when treated with a combination of cyclic FMD and standard systemic treatments in the context of the NCT03340935 trial. Conclusion: These excellent responses prompt the initiation of clinical trials to investigate cyclic FMD in combination with standard antitumour therapies in specific clinical contexts. Highlights: In the NCT03340935 trial, patients received cyclic FMD plus with standard therapies. One patient with ES SCLC achieved CR (40 Mo.) with FMD plus pembrolizumab. One patient with mPDAC achieved CR (52 Mo.) with FMD plus abraxane–gemcitabine. One patient with mKRAS mut  CRC achieved CR (42 Mo.) with FMD plus XELIRI–bevacizumab. Two mTNBC patients achieved CR (36 Mo., 25 Mo.) with FMD plus CBDCA + gemcitabine.